Reading & Reflection Journal - Hagemeister, Annelies (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Each week a set of reading and reflection questions and online exercises are posted for the following week. These are designed for students to use when they are reading the text in order to focus their reading and prepare for the next class period. As a way to integrate the readings for the week, discussion in class, and other class activities, speakers, and films, you are asked to develop journal entries.